Kadar Timbal (Pb) Pada Rambut dan Kuku Polisi Lalu Lintas di Kota Pekanbaru dan Kota Bengkalis - Wahyu Hardinsyah Putra; Bintal Amin; Sofia Anita (Universitas Riau, 2015)
This research was conducted in the city of Bengkalis and Pekanbaru from June toAugust 2014, with the aim to analyze the concentrations of lead (Pb) in hair andnails of traffic policemen and to analyze the relationship between the length ofemployment with concentrationss of lead contained in hair and nails of traffic police in thecity of Bengkalis and Pekanbaru. The samples were analyzed in the Laboratory of PhysicalChemistry of the Faculty of Mathematics and Natural Sciences, University of Riau by usingAAS (Atomic Absorption Spectrophotometer). Results of the research showedthat lead concentrations in hair and nails of traffic policemen in the city of Pekanbaruwere 13.36 and 2.11 ppm resprctively and categorized as medium and low level ofcontamination. Meanwhile, lead concentrations in hair and nails of traffic policemen in thecity of Bengkalis were 21.81 and 2.56 ppm which were also categorized as medium and lowlevel of contamination respectively. Concentrations of Lead in the hair of policemen relationto length of employment in Bengkalis were 14.37; 13.09 and 25.29 ppm for <3, 3-5 and >5years respectively. Lead concentrations in nails of traffic policemen at both locations for awork period <3, 3-5 and >5 years were 1.58, 2.70 and 2.71ppm respectively. Average Leadconcentrations in the hair (17.56 ppm) was higher than in nails (2.33 ppm), however theirconcentrations were statistically not different.